2019
DOI: 10.4028/www.scientific.net/msf.945.1036
|View full text |Cite
|
Sign up to set email alerts
|

Sludge of the Fuel-Energy and Oil-Producing Complex in the Production of Wall Ceramic Products

Abstract: The experience of using slime wastes in the production of wall ceramic bricks is considered. The results of the investigation of clayey raw materials in the deposits of the Western Orenburg region and technogenic wastes of the fuel-energy and oil-producing complex are analyzed with an analysis of their effect on the properties of wall ceramics: density, strength, and water absorption. Based on the results of the research, optimal compositions were developed using ash and slag wastes in a composition with alumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…1) after separate grinding showed that it was possible to obtain the ceramic brick brands from M120 to M225 with satisfying physical and mechanical properties, where the average density is in the range from 1,6 to 1,98 g / cm 3 and with water absorption 12-14 %. The selected areas determine the optimal pressure in the range from 19,5 to 20,5 MPa, which is confirmed by the previous studies [6]. By changing the amount of molding moisture in the press powder of the recommended composition from 8 to 12 % and the spent pressing pressure of 20 MPa (Fig.…”
Section: Materials and Technologies In Construction And Architecture IIsupporting
confidence: 82%
See 2 more Smart Citations
“…1) after separate grinding showed that it was possible to obtain the ceramic brick brands from M120 to M225 with satisfying physical and mechanical properties, where the average density is in the range from 1,6 to 1,98 g / cm 3 and with water absorption 12-14 %. The selected areas determine the optimal pressure in the range from 19,5 to 20,5 MPa, which is confirmed by the previous studies [6]. By changing the amount of molding moisture in the press powder of the recommended composition from 8 to 12 % and the spent pressing pressure of 20 MPa (Fig.…”
Section: Materials and Technologies In Construction And Architecture IIsupporting
confidence: 82%
“…At the initial stage of the research, the granulometric composition of the initial clay raw material and ASW as a corrective additive was determined (Table 3). The required amount of ash and slag waste in the charge should be 28 % by weight was established based on the exploratory experiments [6]. Since loams contain a large number of quartz inclusions with a melting point of 1450 ° C, an additional silicate-lump of melt is introduced in the amount of 10 % by mass, to form a sufficient number of melted eutectics and to destroy the quartz crystal lattice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the next stage, the technological properties of the clayey raw materials were determined (Table 2). On the basis of the data obtained on the number of plasticity of loam and literary analysis [8][9][10][11], one can judge the feasibility of its use in the production of bricks by the method of semi-dry pressing.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the volume coloring of the product, especially in the case of obtaining saturated color tones, requires an increased consumption of coloring additives, which increases its cost. Reducing the cost of the product in this case is possible due to the use in the compositions of the masses of man-made wastes containing in enough quantity color-forming oxides necessary to give the material the desired color [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The choice of pigments is determined by the properties of the pigment and material, the nature of their interaction, as well as the processing parameters and operating conditions of the products.…”
Section: Introductionmentioning
confidence: 99%